2013
DOI: 10.1159/000350505
|View full text |Cite
|
Sign up to set email alerts
|

Self-Perceived Stigmatization in Female Patients with Anorexia Nervosa - Results from an Explorative Retrospective Pilot Study of Adolescents

Abstract: Background: The stigma of mental illness has been identified as an important barrier to treatment and recovery. Previous research reported the stigmatization of individuals with eating disorders by both health professionals and the general public. The aim of this pilot study was to empirically assess the previous stigmatization and discrimination experiences of young female patients with anorexia nervosa (AN) using a retrospective explorative approach. Methods: An in-house questionnaire that was developed to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 31 publications
2
30
0
2
Order By: Relevance
“…In line with our finding, a previous study on families of people with AN similarly found that stigma towards families rather than stigma towards individuals with this illness was an important predictor of family functioning (Dimitropoulos et al, 2008). The finding 0.56* from our study is further supported by a study of adolescents with eating disorders who reported that they perceived their parents, especially their mothers, as being criticized for the development of their illness (Maier et al, 2014). Qualitative research also suggests that families of people with eating disorders believe that others hold them responsible for their child's illness (Hillege et al, 2006).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In line with our finding, a previous study on families of people with AN similarly found that stigma towards families rather than stigma towards individuals with this illness was an important predictor of family functioning (Dimitropoulos et al, 2008). The finding 0.56* from our study is further supported by a study of adolescents with eating disorders who reported that they perceived their parents, especially their mothers, as being criticized for the development of their illness (Maier et al, 2014). Qualitative research also suggests that families of people with eating disorders believe that others hold them responsible for their child's illness (Hillege et al, 2006).…”
Section: Discussionsupporting
confidence: 91%
“…Negative stereotypes of people with AN are held by the general public, college age students, and service providers (Crisafulli et al, 2008;Geerling and Saunders, 2015;Iles et al, 2015;Puhl and Suh, 2015;Stewart et al, 2006Stewart et al, , 2008. In contrast to other mental illnesses, AN evokes significant envy and admiration of the person with AN for achieving weight loss and obtaining self-control over eating (Geerling and Saunders, 2015;Holliday et al, 2005;Katterman and Klump, 2010;Maier et al, 2014;Mond et al, 2006;Roehrig and McLean, 2010;Stewart et al, 2006;Zwickert and Rieger, 2013). Researchers have begun to shift their attention from examining stigma from the perspective of the general public to investigating the internalization of stigma in those experiencing and living with this mental illness (Griffiths et al, 2015a(Griffiths et al, , 2015b).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies in the present review reported stigmatizing attitudes of families, friends and health professionals surrounding eating disorders, a phenomenon described by Griffiths, Christensen, Jorm, Evans, and Groves as perceived stigma. Similarly, previous research has shown that adult women with eating disorder symptoms believed that people with bulimia nervosa would be discriminated against and they might therefore not wish to disclose their problems .…”
Section: Discussionmentioning
confidence: 74%
“…In addition, studies with patient groups indicate that individuals with EDs are acutely sensitive to disparaging attitudes, which can either be internalised or construed as a deterrent to service engagement (Easter, 2012;Maier et al 2014). Stigmatising attitudes held by healthcare providers may, therefore, impair the experience, extent and quality of the care available to young people with EDs.…”
Section: Healthcare Professionals' Attitudes Towards Edsmentioning
confidence: 99%